2021
DOI: 10.1007/s10916-021-01795-8
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Macular Edema Screened by Handheld Smartphone-based Retinal Camera and Artificial Intelligence

Abstract: Our aim was to assess the tomographic presence of diabetic macular edema in type 2 diabetes patients screened for diabetic retinopathy with color fundus photographs and an artificial intelligence algorithm. Color fundus photographs obtained with a low-cost smartphone-based handheld retinal camera were analyzed by the algorithm; patients with suspected macular lesions underwent ocular coherence tomography. A total of 366 patients were screened; diabetic macular edema was suspected in 34 and confirmed in 29 indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Although the AI system is less sensitive than optical coherence tomography in screening for diabetic macular edema, studies have shown that the AI system has high sensitivity and specificity for DR detection including diabetic macular edema. 50 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the AI system is less sensitive than optical coherence tomography in screening for diabetic macular edema, studies have shown that the AI system has high sensitivity and specificity for DR detection including diabetic macular edema. 50 …”
Section: Discussionmentioning
confidence: 99%
“…Although the AI system is less sensitive than optical coherence tomography in screening for diabetic macular edema, studies have shown that the AI system has high sensitivity and specificity for DR detection including diabetic macular edema. 50 Some limitations of this study should be mentioned. First, this study was a cross-sectional investigation, which does not allow conclusions on risk factors, but allows conclusions on associated risk factors for DR. Second, as a hospitalbased study, the patients recruited in the study may not be representative of the overall population with diabetes.…”
Section: Dovepressmentioning
confidence: 91%
“…Their possible usage for monitoring anticoagulant therapy should therefore be seen as another important opportunity, which thus extends their usage for chronic disease monitoring (e.g., for measuring hemoglobin in patients with anemia, glycosylated hemoglobin in those with diabetes, and so forth). 20‐24 Nonetheless, some important aspects still need to be defined before they will be ready for prime time in VKAs monitoring (e.g., is self‐adjustment of VKA therapy reliable using the device? How does one check the proper function of the device?…”
Section: Discussionmentioning
confidence: 99%
“…Although the authors have defined referable DR as DR equal to or worse than moderate non proliferative DR ( 6 ), diabetic macular edema (DME) is more common than proliferative DR and corresponds to the predominant cause of moderate or severe vision loss in patients with diabetes ( 7 ). Even though it is challenging to identify DME in bi-dimensional color fundus photographs, a valid alternative could be a semi-automated strategy combined with a higher sensitivity ( 8 ), with or without telemedicine evaluation by specialists ( 9 ); a two-tiered evaluation involving the more expensive optical coherence tomography (OCT) machines could be advised only for those with suspected macular edema ( 8 ). Certainly, the scarcity of ophthalmic medical resources mentioned by the authors has to be taken into account in evaluating the trade-off between sensitivity and specificity ( 6 ); since referrals incur costs for the patient and the health-care system ( 10 ), and since cost considerations are essential for the sustainability screening programmes, a formal economic evaluation would be warranted for the ideal calibrations of such operating points ( 9 ).…”
mentioning
confidence: 99%
“…Along with AI, which has been reported to allow higher referral adherence from point-of-care screening recommendations ( 10 ), other tools have been proposed to achieve higher coverage and adherence rates, even in settings where eyecare is readily available, such as telemedicine ( 12 ). Telemedicine protocols, besides having been proven cost-effective for this use case ( 13 ), are all the more remarkable in China considering its dimensions, the fact that the majority of patients at high risk live in rural areas ( 14 ), and the possibility of employing mobile units and portable retinal cameras ( 8 ). Furthermore, raising awareness about DR among patients and local health-care workers is essential for increased attendance and the overall success of screening initiatives ( 9 ).…”
mentioning
confidence: 99%